Variation of absorbed photosynthetically active radiation (APAR) and yield of different kharif rice cultivars influenced by date of transplanting - ASIS MUKHERJEE; SAON BANERJEE; SUMAN SAMANTA; CHAKRABORTY AGNISWAR JHA; NABAJYOTI DEKA (Journal of Agrometeorology, 2013)
A field experiment was conducted at BCKV, Kalyani, West Bengal (Latitude 22°58’60 N, Longitude 88°28’60 E) to evaluate the performance of different rice cultivars grown during kharif season of 2010 and 2011. The experiment was laid down in a split-plot design where three dates of transplanting (D1: 15th June; D2: 29th June and D3: 13th July) for both the years were allotted as main plot treatment and three rice cultivars (V1: Satabdi ; V2: Baishmukhi ; V3: Pre-Release) was considered as sub-plot treatment. Date of transplanting significantly influenced the grain yield. It was at the highest under D1 which reduced gradually with delay in transplanting. Among different varieties, Satabdi produced the highest yield (4079 kg ha-1). Irrespective of variety, absorbed photosynthetically active radiation (APAR) value increased with the advancement of crop growing season and it was at the highest level during panicle initiation stage. In general, the highest APAR value (90.2 μMol m-2s-1) was recorded under pre-released variety during panicle initiation stage due to its leaf orientation which was declined by 14% and 19.5% respectively under Baishmukhi and Satabdi variety.